Roles of α(2)-adrenoceptors and glutamate mechanisms in the external urethral sphincter continence reflex in rats - Furuta, Akira (2009)
PURPOSE: To investigate the role of α(2)-adrenoceptors (ARs) and glutamate mechanisms of the urethral continence reflex in response to abdominal pressure increases. MATERIALS AND METHODS: Under urethane anesthesia, external urethral sphincter (EUS)-electromyogram activity was evaluated in spinal cord transected (T8-9) female rats during lower abdominal wall compression before and after intravenous (i.v.) application of test drugs. The effects of MK-801 (0.03, 0.3 and 3 mg/kg i.v.), an N-methyl-D-aspartate glutamate receptor antagonist, or medetomidine (0.03, 0.3 and 3 mg/kg i.v.), an α(2)-AR agonist, on EUS activity were examined. Then, idazoxan (0.3 mg/kg i.v.), an α(2)-AR antagonist, was administered before or after application of MK-801 (1 mg/kg i.v.). In addition, idazoxan (0.3 mg/kg i.v.) was administered following application of duloxetine (1 mg/kg, i.v.), a serotonin/norepinephrine reuptake inhibitor. RESULTS: Both MK-801 and medetomidine dose-dependently decreased the EUS activity. Idazoxan significantly increased the EUS activity by 64%, but the increase in EUS activity after idazoxan was abolished by MK-801. On the other hand, idazoxan did not reverse the inhibitory effects of MK-801. In addition, idazoxan significantly potentiated the duloxetine effects on the EUS activity by 120%. CONCLUSIONS: These results indicate that: 1) glutamate is a major excitatory neurotransmitter in the urethral continence reflex response to abdominal pressure increases, 2) α(2)-AR activation suppresses EUS activity probably via presynaptic inhibition of glutamate release and 3) the effects of serotonin/norepinephrine reuptake inhibitors are enhanced by α(2)-AR inhibition. Therefore, α(2)-AR antagonists could be beneficial for the treatment of stress urinary incontinence.